Measuring system of systems performance. (1st January 2012) - Meyers, Thomas J.; Hester, Patrick T.
Single systems and systems of systems, alike, demand management approaches focused on performance; but system of systems management can only responsibly address performance if it accounts for characteristics such as the presence of distinct subsystems pursuing possibly disparate purposes, a characteristic by definition of no concern to single system management. By extension then, with to manage in many ways to measure, systems of systems demand performance measurement schemes that accommodate the traits that set them apart from individual systems. Enterprise AID represents a means for measuring and hence managing the current or future performance of systems of systems. Enterprise AID – or simply AID, for assessment, improvement, and design – is a methodology for the design and use of performance measurement systems able to uniformly address problems encountered with extant or envisioned, single system or system of systems type enterprises. This paper describes advantages held by the AID methodology for system of systems performance measurement, and it does so within a context set by appropriate definitions, selected methodology elements, and an application example focused on the selected elements. This paper concludes with a recognition of performance related issues attendant to system of systems improvement or design.